Design and Optimization of an Integrated Visible Light Communication and Localization System Using Liquid Crystal Based-RIS Receivers - Raphael Ahiaklo-Kuz; Sylvester Aboagye; Omar Maraqa; Telex M. N. Ngatched (IEEE Photonics Journal)
Visible Light Communication (VLC) is emerging as a pivotal technology in next-generation wireless networks, leveraging the abundant unlicensed spectrum to achieve ultra-high data rates with minimal energy overhead. This paper presents the design and optimization of a novel integrated VLC and localization (VLCL) system enhanced by liquid crystal-based reconfigurable intelligent surfaces (LC-RISs). The proposed system architecture facilitates simultaneous communication, localization, and illumination within indoor environments by dynamically adjusting the refractive index of the LC-RIS under an electric field to precisely control light propagation and focus. We address two core optimization challenges: sum rate maximization and energy efficiency maximization, both of which are formulated as constrained optimization problems. While the sum rate problem is convex and solvable using standard optimization techniques, the energy efficiency problem is non-convex, necessitating the development of a low-complexity solution via fractional programming. Simulation results substantiate the efficacy of the LC-RIS in significantly enhancing both sum rate and energy efficiency, particularly in scenarios with dense number of users and access point configurations, thereby demonstrating the LC-RIS's potential to substantially improve the performance of VLCL systems.